2017
DOI: 10.1002/14651858.cd009460.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Uric acid lowering therapies for preventing or delaying the progression of chronic kidney disease

Abstract: Uric acid lowering therapies for preventing or delaying the progression of chronic kidney disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 40 publications
1
46
0
2
Order By: Relevance
“…Tubulointerstitial fibrosis is a common feature of various kidney diseases which are associated with CKD progression to ESRD. A higher UA level is associated with a significant decline in eGFR and a higher risk of kidney failure [ 24 , 25 ]. In vivo, UA displays both an anti- and pro-oxidant role, which is dependent on the biological conditions [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tubulointerstitial fibrosis is a common feature of various kidney diseases which are associated with CKD progression to ESRD. A higher UA level is associated with a significant decline in eGFR and a higher risk of kidney failure [ 24 , 25 ]. In vivo, UA displays both an anti- and pro-oxidant role, which is dependent on the biological conditions [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated levels of serum uric acid have been associated with increased cardiovascular risk and CKD (63)(64)(65) . In this context, it has been suggested that lowering serum uric acid may improve kidney function (66,67) .…”
Section: Discussionmentioning
confidence: 99%
“…51 At present, there is insufficient evidence to recommend treatment of asymptomatic hyperuricemia with the purpose of delaying the progression of CKD. 52,53…”
Section: Step 7 Initiation Titration and Optimization Of Tolvaptanmentioning
confidence: 99%